PERBEDAAN KADAR CO DAN SO2 DI UDARA BERDASARKAN VOLUME LALU LINTAS DAN BANYAKNYA POHON DI JL. DR. MANSYUR DAN JL. JENDRAL A.H. NASUTION DI KOTA MEDAN TAHUN 2015 - cut tatiana; indra chahaya; wirsal hasan (Lingkungan dan Kesehatan Kerja, 2015)
Abstract Air pollution in urban area dominated by as much as 70% by vehicle activity. Carbon monoxide (CO) and sulfur dioxide (SO2) are included as the pollutants that produced by vehicle and also included as air quality parameters. If the concentration in air exceeds the quality standard can cause health promblems for humans. The objective of research would be to know the difference of CO and SO2 concentration in air by virtue of the traffic volume and quantity of tree at Jl. Dr. Mansyur and Jl. Jend. A.H. Nasution in Medan city for 2015. This research used survey and descriptive method in order to know the description about difference of CO and SO2 concentrations in air by virtue of traffic and quantity of tree at Jl. Dr. Mansyur and Jl. Jend. A.H. Nasution in Medan city for 2015. The result of research the highest concentration of CO and SO2 were found at Jl. Jend. A.H. Nasution with the highest traffic volume and less of tree with the number of CO is 17.750 µg/Nm3 and the number of SO2 is 69,93 µg/Nm3, while the lowest concentration of CO and SO2 were found at Jl. Dr. Mansyur with the lowest traffic volume and many more of tree with the number of CO is 9.161 µg/Nm3 and the number of SO2 is 59,05 µg/Nm3. The conclusions of this research is concentrations of CO and SO2 were found on highway with high traffic volume and less of tree. Therefore it would be necessary to grow tree or other plant that can assorb air pollutant on the highway with hectic traffic acitivity.